Assessment of the Risk of Cardiovascular Diseases and its Relationship with Heart Rate Variability in Physically Active and Sedentary Individuals - Sousa, Monize de Melo e; Figueiredo Xavier, Lourdes Carolina; Pereira, Raphael do Nascimento; de Pontes Miranda, Cláudia Jeane Claudino (International Journal of Advanced Engineering Research and Science, 2023)
Heart rate variability (HRV) is the ability of the heart muscle to adapt to changes imposed on the heart. Therefore, a low baseline HRV may indicate a dysfunction of the autonomic nervous system and lead to the development of cardiovascular diseases (CVD). Thus, the objective of the study was to evaluate and compare HRV with the risk of developing CVD in sedentary and physically active individuals. This is an exploratory, experimental, applied study, with cross-sectional design, under ethical opinion number: 5,581,838. In the sample, 24 individuals of both genders, between 30 and 55 years old, were divided into a sedentary group and another physically active group, excluding those who were not within the inclusion criteria and who had clinically diagnosed cardiovascular or cardiopulmonary diseases. . For data collection, the International Physical Activity Questionnaire and the Cardiovascular Risk Stratification Questionnaire were applied; HRV was verified through the Polar H10 cardiac sensor, blood pressure, weight, height and abdomen-hip circumference. The sedentary group had a higher cardiovascular risk when assessing BMI, waist circumference and waist-hip ratio. Furthermore, the results showed, in sedentary individuals, a significantly higher value of systolic and diastolic blood pressure (124.66±8.91 versus 114.50±9.58 - 84.75±7.02 versus 75.66±6, 38, respectively) and heart rate (74.25±7.96 versus 67.41±7.67) when compared to physically active individuals, which associated with HRV data (42.91±7.54 versus 54.75 ±6.82), time domain and frequency domain, suggest greater sympathetic activity to the detriment of parasympathetic activity in sedentary individuals, reinforcing the cardiac autonomic imbalance in this group.